Comparison between conduction system pacing and cardiac resynchronization therapy in right bundle branch block patients - Strocchi, Marina; Gillette, Karli; Neic, Aurel; Elliott, Mark K.; Wijesuriya, Nadeev; Mehta, Vishal; Vigmond, Edward J.; Plank, Gernot; Rinaldi, Christopher A.; Niederer, Steven A. (Frontiers in Physiology, 2022)
A significant number of right bundle branch block (RBBB) patients receive cardiac resynchronization therapy (CRT), despite lack of evidence for benefit in this patient group. His bundle (HBP) and left bundle pacing (LBP) are novel CRT delivery methods, but their effect on RBBB remains understudied. We aim to compare pacing-induced electrical synchrony during conventional CRT, HBP and LBP in RBBB patients with different conduction disturbances, and to investigate whether alternative ways of delivering LBP improve response to pacing. We simulated ventricular activation on twenty-four four-chamber heart geometries each including a His-Purkinje system with proximal right bundle branch block (RBBB). We simulated RBBB combined with left anterior and posterior fascicular blocks (LAFB and LPFB). Additionally, RBBB was simulated in the presence of slow conduction velocity (CV) in the myocardium, left ventricular (LV) or right ventricular (RV) His-Purkinje system, and whole His-Purkinje system. Electrical synchrony was measured by the shortest interval to activate 90% of the ventricles (BIVAT-90). Compared to baseline, HBP significantly improved activation times for RBBB alone (BIVAT-90: 66.95.5ms vs 42.63.8ms, P<0.01), with LAFB (69.55.0ms vs 58.16.2ms, P<0.01), with LPFB (81.86.6ms vs 62.96.2ms, P<0.01), with slow myocardial CV (119.411.4ms vs 97.210.0ms, P<0.01) or slow CV in the whole His-Purkinje system (102.37.0ms vs 75.55.2ms, P<0.01). LBP was only effective in RBBB cases if combined with anodal capture of the RV septum myocardium (BIVAT-90: 66.95.5ms vs 48.25.2ms, P<0.01). CRT significantly reduced activation times in RBBB in the presence of severely slow RV His-Purkinje CV (95.17.9ms vs 84.39.3ms, P<0.01) and LPFB (81.86.6ms vs CRT: 72.98.6ms, P<0.01). Both CRT and HBP were ineffective with severely slow CV in the LV His-Purkinje system. HBP is effective in RBBB patients with otherwise healthy myocardium and Purkinje system, while CRT and LBP are ineffective. Response to LBP improves when LBP is combined with RV septum anodal capture. CRT is better than HBP only in patients with severely slow CV in the RV His-Purkinje system, while CV slowing of the whole His-Purkinje system and the myocardium favor HBP over CRT.